Human Pluripotent Stem Cells in Neurodegenerative Diseases: Potentials, Advances and Limitations - Kolagar, Tannaz Akbari; Farzaneh, Maryam; Nikkar, Negin; Khoshnam, Seyed Esmaeil (Current stem cell research & therapy, 2020)
Neurodegenerative diseases are progressive and uncontrolled gradual loss of motor neurons function or death of neuron cells in the central nervous system (CNS) and the mechanisms underlying their progressive nature remain elusive. There is urgent need to investigate therapeutic strategies and novel treatments for neural regeneration in disorders like Alzheimer's disease (AD), Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS), and multiple sclerosis (MS). Currently, the development and identification of pluripotent stem cells enabling the acquisition of a large number of neural cells in order to improve cell recovery after neurodegenerative disorders. Pluripotent stem cells which consist of embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) are characterized by their ability to indefinitely self-renew and the capacity to differentiate into different types of cells. The first human ESC lines were established from donated human embryos; while, because of a limited supply of donor embryos, human ESCs derivation remains ethically and politically controversial. Hence, hiPSCs-based therapies have been shown as an effective replacement for human ESCs without embryo destruction. Compared to the invasive methods for derivation of human ESCs, human iPSCs has opened possible to reprogram patient-specific cells by defined factors and with minimally invasive procedures. Human pluripotent stem cells are a good source for cell-based research, cell replacement therapies and disease modeling. To date, hundreds of human ESC and human iPSC lines have been generated with the aim of treating various neurodegenerative diseases. In this review, we have highlighted the recent potentials, advances, and limitations of human pluripotent stem cells for the treatment of neurodegenerative disorders.